Accessory cavitated uterine malformation: a diagnostic challenge of an unclassified rare presentation - Gupta, Shagun; Kulshreshtha, Anshul; Kothari, Aarti; Shekhawat, Usha; Shah, Divya; Malhotra, Sonali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Mullerian anomalies are rare anomalies of female genital tract with prevalence of around 5%. Accessory cavitated uterine malformation (ACUM) is a cavitated lesion surrounded by a rim of myometrium, located below the insertion of round ligament and fallopian tubes. A normal uterine cavity with visualisation of both ostia is must to differentiate with non-communicating uterine horn. ACUM presents as severe dysmenorrhoea in females below 30 years of age. It is not included in revised ASRM or ESHRE classification. Diagnostic modalities include 3D ultrasonography and MRI. Medical management including estrogen/progesterone oral contraceptives, nonsteroidal anti-inflammatory drugs (NSAIDs), the progesterone-only pill proves to be ineffective in most of the patients. Most articles mentioned laparoscopic excision of ACUM as the main management. Some papers also mentioned cornual excision or hysterectomy as the treatment modality. Sclerotherapy has also been tried as a conservative management. Fertility has also improved post-surgery of ACUM.